Diseño del conector central en el corredor turístico del Malecón de Quevedo - Macías Hugo, José Romario (2025)
The present research work addresses the design of the central connector in the tourist corridor of the Malecón de Quevedo, an architectural proposal that seeks to enhance urban integration, improve mobility and strengthen the cultural identity of the sector. The planning of this space responds to the need to create a functional and attractive connection point that articulates the different areas of the boardwalk, promoting tourism and local economic revitalization. The study is based on a detailed analysis of the site and its surroundings, considering aspects such as topography, vegetation, urban equipment, roads and pedestrian and vehicular mobility. From these factors, design principles are established based on accessibility, sustainability and functionality, guaranteeing an inclusive and efficient space. Which incorporates an aesthetic proposal inspired by the figure of the horse, whose analogy translates into curved and dynamic shapes that give identity and fluidity to the design. The integration of green areas and appropriate street furniture reinforces the recreational and landscape nature of the project, generating an attractive environment for residents and visitors. In conclusion, the design of the central connector on the Malecón de Quevedo represents a strategic solution to improve connectivity and enhance tourism in the city, providing a modern, accessible space in harmony with the environment.